PERMAINAN SAINS BAGI SISWA-SISWI SEKOLAH SMP SWASTA GITA SURYA DAN SMA NEGERI 1 EBAN KECAMATAN MIOMAFO BARAT KABUPATEN TIMOR TENGAH UTARA - Sefrinus M.D. Kolo; Yohana Ivana Kedang; Maria M Kolo; Jefry Presson; Elisabeth Korbafo; Eduardus Edi; Noviana M Oebenu; Regina Seran (LPPM Universitas Timor, 2019)
Community service was held on November 17, 2018 at Gita Surya Private Middle School and Eban 1 Public High School. The material for the dedication of science games is fruit electricity, electrolyte solution, caramelization of sugar, magic money, electric magnets, differences in air pressure, floating and floating floating events, volcanic eruptions, mothballs moving in water, natural acid-base indicators. Science demonstration activities carried out with methods of performance, lectures and discussions. Students interact actively, not rigidly, energetically marked by the number of questions that arise, and students are very enthusiastic in answering questions given by the service team and the high interest of students to be involved in the practice of science demonstrations.